Flight of the alone to the alone - Osho (New Delhi, 2011)
The ancient Kaivalya Upanishad is a search for ultimate freedom. It begins with a prayer to strengthen the senses. It takes great individual effort to become free, says Osho, but before making that effort, a greater, existential power has to be invoked: 'the first effort'. Embracing the senses is not a sign of weakness or indiscipline. The senses are, on the contrary, the door to experiencing the divine, a means to freedom. Often people misunderstand this, calling that which comes within the grasp of our sense organs 'the world' and that which doesn't, 'the divine'. According to this Upanishad and to Osho, both are divine. That is why Osho continually emphasizes the importance of love, celebration, creativity and humour on the path of awareness. Flight of the Alone to the Alone brings together a series of talks given by Osho on the Kaivalya Upanishad. It explores the nature of existence and tackles some of life's most fundamental challenges: achievement, loneliness, the eternal quest for happiness, and freedom.
Keywords: Meditation